Health Belief Model of Buton's Ethnic Migration Population the Birthplace Selection in South Buru Island's - Nancy Olii; Salman Salman; Nurnaningsih Ali Abdul; Siti Choirul Dwi Astuti; Hasnawatty Surya Porouw; Selvi Mohamad; Juli Gladis Claudia; Eka Rati Astuti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Birthplace can be influenced the social and cultural background of the Butonese women. Traditions, customs, and socio-cultural hereditary are maintained when facing childbirth at home. This study aims to explore the socio-cultural aspects of the Butonese ethnicity in the choice of place of delivery in Waesama District, Kepala Madan District, and Leksula District in South Buru Regency. This method uses a type of qualitative research with an ethnographic design, conducted in-depth interviews with 17 informants obtained by purposive sampling. From the results of the study, it was shown that from a social aspect, Butonese women gave birth in a health facility, the disgrace of their family and private parts would be seen and known by others, so they should give birth at home because we have separate treatments that cannot be done by health workers. The cultural aspects of the tradition that are maintained are in the form of ritual confessions and predictions for the birth of a baby. The rituals are in the form of Piago between husband and wife, Piago using Kabenci, Prayer, Kotika, waiting for the tides and low tides, and Pikilala.  Tempat bersalin dapat dipengaruhi oleh latar belakang sosial dan budaya perempuan etnis Buton. Tradisi, adat istiadat, dan sosial budaya secara turun temurun tetap terjaga saat menghadapi persalinan dirumah.Penelitian ini bertujuan untuk mengeksplorasi aspek sosial budaya etnis Buton dalam pemilihan tempat bersalin di Kecamatan Waesama, Kecamatan Kepala Madan, dan Kecamatan Leksuladi Kabupaten Buru Selatan.Metode ini menggunakan jenis penelitian kualitatif dengan rancangan Etnografi,dilakukan wawancara mendalam terhadap17 informan yang didapatkan dengan purposive sampling.Dari hasil penelitian menunjukkan perempuan Butondari aspek sosial, persalinan di fasilitas kesehatan maka aib keluarga dan aurat mereka akan terlihat dan diketahui oleh orang lain, hendaklah bersalin di rumah karena kita mempunyai penanganan tersendiri yang tidak bisa dilakukan oleh tenaga kesehatan. Aspek budaya dari tradisi yang dijaga yaitu berupa ritual pengakuan dosa dan ramalan terhadap kelahiran seorang bayi. Ritual tersebut berupa Piago antar suami istri, Piago menggunakan Kabenci, baca doa, Kotika, menunggu air pasang dan surut, dan Pikilala